La falta de regulación normativo al depósito de garantía en contrato de arrendamiento - Orozco Suque, Edwin Javier (2025)
This paper presents a study on the lack of regulatory regulation of the security deposit in rental contracts in Ecuador, analyzing its impact on legal security between tenants and landlords. The main objective is to thoroughly explore the dynamics affecting both parties due to the absence of a clear and specific legal framework. A qualitative methodology based on interviews with 25-30 participants is used. Thematic coding analyzes perceptions about how the regulation affects legal security. The results (Chapters IV and V) reveal social, economic, and legal implications, providing input for public policies that regulate leasing and foster a more equitable environment. In conclusion, the study seeks to demonstrate that the lack of specific regulation on security deposits in rental contracts generates uncertainty, vulnerability, and potential abuse, affecting the right to housing and trust in the legal system. The findings are expected to prompt the creation of a legal framework that promotes equity and security in rental contracts, benefiting tenants and landlords and strengthening the social fabric.